2011
DOI: 10.1097/01.sa.0000407044.50521.76
|View full text |Cite
|
Sign up to set email alerts
|

Reversibility of Rocuronium-Induced Profound Neuromuscular Block With Sugammadex in Younger and Older Patients

Abstract: A lthough chronological age is a well-established risk factor for developing cardiovascular diseases, the changes that accumulate with age are highly variable. It has been increasingly recognized that indices of vascular age are more reliable than age per se in prediction of adverse cardiovascular outcomes. Variations in the way these age-related changes occur are a function of many genetic and environmental factors. Some of the pathophysiological mechanisms that characterize the vascular aging phenotype are r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 5 publications
(5 reference statements)
1
26
0
Order By: Relevance
“…The results of Suzuki and colleagues [29] suggest that appropriate use of sugammadex is associated with the absence of both residual neuromuscular blockade and severe respiratory events in the PACU. However, there have been reports of residual neuromuscular blockade in specific clinical situations.…”
Section: Discussionmentioning
confidence: 91%
“…The results of Suzuki and colleagues [29] suggest that appropriate use of sugammadex is associated with the absence of both residual neuromuscular blockade and severe respiratory events in the PACU. However, there have been reports of residual neuromuscular blockade in specific clinical situations.…”
Section: Discussionmentioning
confidence: 91%
“…In elderly patients, in addition to atherosclerotic changes, decrease in cardiac output, HR and muscular blood flow rate leads the onset of the effect of reversal agents, like other drugs, to be delayed (12). As a consequence of the decrease in regional blood flow, the duration of NMBA's and sugammadex effect is elongated (10,11). A slower increase in the plasma concentration of sugammadex gives rise to slower diffusion of rocuronium from neuromuscular junction.…”
Section: Resultsmentioning
confidence: 99%
“…In the study of Suzuki et al (10), while post tetanic count (PTC) was 1-2, the reversal effect of sugammadex (4 mg/kg) on neuromuscular blocking was investigated on 30 female patients monitored with acceleromyography, and it was found that the duration of the effect of sugammadex was prolonged three fold in older patients (aged ≥70) compared to younger patients (aged 20-50). This was attributed to the delay in the duration of the effect of sugammadex owing to the decrease in cardiac output and muscular blood flow in the elderly.…”
Section: Resultsmentioning
confidence: 99%
“…The number of visible PTC responses is inversely related to the depth of the blockade, and it can be used as a guide either to predict the time remaining until recovery of visible TOF response [1][2][3][4][5][6] or to determine the dose of sugammadex or other reversal agents required for adequate reversal. 7 The PTC technique relies on inducing a transient improvement of neuromuscular transmission in the monitored muscle, usually the adductor pollicis. It follows that an artificial recovery is produced only in that muscle and that subsequent responses to single or TOF stimulation might be spuriously elevated.…”
Section: Résumémentioning
confidence: 99%